Continuous Passive Motion Does Improve Range of Motion, Pain and Swelling After ACL Reconstruction: A Systematic Review and Meta-Analysis - Jaspers, Theo; Taeymans, Jan; Hirschmüller, Anja; Baur, Heiner; Hilfiker, Roger; Rogan, Slavko (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
Background This systematic review and meta-analysis evaluates the results of empirical studies on the effects of CPM on rehabilitation after ACL reconstruction. The research question was: what are the effects of CPM on ROM, swelling and pain after ACL reconstruction?Patients/Material and Methods We searched in MEDLINE, Embase, CINAHL, Cochrane and PEDro up to January 2018. Standardized mean differences (SMD) were expressed as Hedgesʼ g, in order to correct for overestimation of the true effect in small study samples. The 95% confidence intervals (95% CI) were calculated for both the individual studies and the overall weighted estimate. Outcomes were range of motion, pain and swelling.Results Eight studies comprising 442 participants were included in the meta-analysis. Beneficial effects of CPM could be identified for the need for pain medication (Hedgesʼ g = 0.93; 95% CI = 0.41 to 1.45 during the first 24 hours after surgery), the number of PCA button pushes by the patient during the first 24 hours after surgery (MD = 31.20; 95% CI = 11.35 to 51.05), on regaining knee flexion on the third to the seventh postoperative day (MD = 11.6°; 95% CI = 1.96 to 21.33) as well as in the third to the sixth postoperative week (Hedgesʼ g = 0.93; 95% CI = 0.41 to 1.44) and on swelling of the knee in the fourth to sixth postoperative week (Hedgesʼ g = 0.77; 95% CI = 0.35 to 1.18).Conclusion This meta-analysis suggests that CPM has beneficial effects on pain reduction during the first two postoperative days, on knee flexion during the first to the sixth postoperative weeks and on swelling between the fourth and the sixth postoperative weeks. However, the risk-of-bias scores do not allow a high level of evidence.
Keywords: continuous passive motion therapy; anterior cruciate ligament reconstruction; rehabilitation